2017
DOI: 10.1155/2017/7901670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peony‐Glycyrrhiza Decoction on Amisulpride‐Induced Hyperprolactinemia in Women with Schizophrenia: A Preliminary Study

Abstract: Objective The aim of this study is to observe the effect of Peony-Glycyrrhiza Decoction (PGD) on hyperprolactinemia in women with schizophrenia induced by Amisulpride. Material and Methods A total of 41 female schizophrenia patients receiving Amisulpride were randomly divided into placebo (n = 20) and PGD groups (n = 21). Maintaining the original Amisulpride dose, the two groups were given placebo and PGD, respectively. The levels of Prolactin (PRL) and other hormones were measured on the initial day and at we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…As previously reported by Yang et al (2017), the anterior pituitary D 2 receptor can be blocked by amisulpride, subsequently diminishing the inhibitory effect of dopamine secretion, and inducing an increase in PRL. The findings of that study are consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As previously reported by Yang et al (2017), the anterior pituitary D 2 receptor can be blocked by amisulpride, subsequently diminishing the inhibitory effect of dopamine secretion, and inducing an increase in PRL. The findings of that study are consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, the level of PRL in patients treated with amisulpride should be closely monitored. Studies have demonstrated that intervention with Chinese herbs, such as Peony-Glycyrrhiza Decoction (Yang et al , 2017), etc., can improve the symptoms of hyperprolactinemia and reduce PRL levels induced by amisulpride, without influencing mental symptoms and other biochemical indexes.…”
Section: Discussionmentioning
confidence: 99%
“…Only two RCTs24 25 reported hyperprolactinaemia-induced symptoms. In one RCT,25 79% of patients in the PGD group and 0% in the placebo group reported improvement in hyperprolactinaemia-induced adverse effects. In another RCT,24 68% of patients on PGD and 54% on placebo reported improvement in hyperprolactinaemia-induced adverse effects.…”
Section: Resultsmentioning
confidence: 99%
“…( 4) Combine with some traditional Chinese medicine, such as Maiya, Sichuan Pepper, dandelions, Achyranthes Bidentata, Ziyin Rougan decoction, and Xiaoyao pills. However, the current studies lack high-level evidence because of their small samples (Yang et al, 2017). ( 5) Recent studies have shown that aripiprazole adjuvant therapy can reduce antipsychoticinduced HPRL with good tolerance (Raghuthaman et al, 2015;Jiang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%